The historical sketch of social tourism development in USSR (Journal of Geography and Environmental Management, 2016)
This article discusses the methodological foundations of organization social tourism in USSR. This article provides information about the history of formation social tourism during communism and socialism. Article covers all period of functioning the Soviet system. Also article gives review to types of social tourism in USSR, some statistics about number of social tourists.
Keywords: Tourism; Social tourism; Tourism in USSR